Maldives : Technical Assistance Report-Public Investment Management Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance Report discusses that in the Maldives, public investment trends have been influenced by a number of contextual factors including the economic dependency on tourism, the high exposure to climate change, and the recent democratization. The mission assessed the strength and quality of public investment management (PIM) in the Maldives using the IMF Public Investment Management framework, based on the three phases of the PIM cycle. The report highlights that the most significant weakness in the PIM and the wider Public Financial Management system is poor budget credibility and budget execution. However, some progress has been made in improving PIM institutions, and reforms are ongoing in a number of areas. It is imperative to strengthen the project appraisal process by developing a standard methodology for project appraisal, publishing this methodology and verifying that it is consistently applied by the line ministries. It is also important to develop a framework for ex-post evaluations and ensure that lessons learned from past projects are incorporated in revised guidelines and practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet